Endogenous sex hormones and risk factors atherosclerosis in healthy Greek postmenopausal women - Lambrinoudaki, I.; Christodoulakos, G.; Rizos, D.; Economou, E.; Argeitis, J.; Vlachou, S; Creatsa, M.; Kouskouni, E.; Botsis, D. (European Journal of Endocrinology, 2006)
Objective: To assess the association between endogenous sex hormones and risk factors for atherosclerosis in healthy postmenopausal women. Design: Cross-sectional study in a university menopause clinic. Methods: Serum sex hormones and lipid-lipoprotein profile, arterial pressure, homocysteine and insulin resistance, measured by the homeostasis model assessment of insulin resistance (HOMA-111), were assessed in 598 healthy postmenopausal women not on hormone therapy. Results: Compared with women in the lowest testosterone quartile (Q), women in the highest testosterone quartile had higher total cholesterol (Q1: 225.2±41.3 vs Q4: 246.2±38.4 mg/dl, P<0.01), low-density lipoprotein (LDL)-cholesterol (Q1: 146.9±37.2 vs Q4: 171.8±35.3 mg/dl, P<0.001), atherogenic index of plasma (AIP) (Q1: -0.224±0.238 vs Q4:-0.087±0.254, P<0.01), apolipoprotein B (ApoB) (Q1: 100.7±23.1 vs Q4: 113.9±23.8 mg/dl, P<0.001) and higher high-density lipoprotein (HDL)-cholesterol (QI: 60.7±14.5 vs Q4: 52.9±13.0 mg/dl, P<0.01). Accordingly, women in the highest free androgen index (FAI) quartile had higher AIP (Q1: -0.232±0.254 vs Q4: -0.078±0.243, P<0.001) and ApoB (Q1: 102.4±25.5 vs Q4: 114.2±25.8mg /dl, P<0.01) and lower HDL-cholesterol (Q1: 62.0±15.7 vs Q4: 51.9±11.6mg/dl, P<0.001) and apolipoprotein A (Q1: 159.6±25.6 vs Q4: 147.9±24.1 mg/dl, P<0.01) compared with women in the lowest FAI quartile. These differences remained significant after adjustment for age, body mass index (BMI), insulin resistance and social habits. The free estrogen index (FEI) exhibited similar associations to the FAL HOMA-IR showed an independent positive association with total testosterone (Q1: 2.00±1.36 vs Q4: 2.66±1.60, P<0.01), FAI (Q1: 1.70±1.12 vs Q4: 3.04±1.66, P<0.001) and FEI (Q1: 1.70±0.91 vs Q4: 3.08±1.77, P<0.001). Conclusions: Increased androgenicity in healthy postmenopausal women is associated with an unfavorable cardiovascular risk profile. High endogenous estradiol is related to a pro-atherogenic lipid profile, an association which may, in part, be mediated by insulin resistance. © 2006 Society of the European Journal of Endocrinology.